2011
DOI: 10.1149/1.3570027
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Degradation by Impurities for Evaluating Life Time of SOFCs

Abstract: The accelerated degradation by impurities was investigated at cathodes with flowing CrO 3 and SO 2 gases. Relatively high pressures (p~10 -8 -10 -4 atm) of CrO 3 and SO 2 were applied to the cathodes and the degradation behaviors were investigated as a function of operation time. The degradation mechanism was examined by considering chemical reactivity and electrochemical reaction at the active cathode/electrolyte interfaces. In the case of CrO 3 poisoning, the relationship between the deposited Cr 2 O 3 amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Due to their excellent catalytic activity for the oxygen reduction reaction, low area-specific resistances can be obtained even at reduced temperatures between 500 and 750 • C. [1][2][3] However, since the interconnectors of SOFCs operating in this temperature range are usually based on chromium-containing alloys (stainless steels), [4][5][6] the stability of these cathodes vs. Cr-poisoning is a key issue. [7][8][9][10][11][12][13][14][15][16][17][18][19] Especially the long-term decrease in the initial high performance of the cathode due to the gas-phase transport of volatile Crspecies and their reaction with the cathode is currently one of the main obstacles for the increase in life-time and reliability of SOFCs. 9,12,14,15 Nevertheless, long-term in-situ studies on the kinetic parameters for oxygen exchange vs. chromium poisoning under defined conditions are scarce.…”
mentioning
confidence: 99%
“…Due to their excellent catalytic activity for the oxygen reduction reaction, low area-specific resistances can be obtained even at reduced temperatures between 500 and 750 • C. [1][2][3] However, since the interconnectors of SOFCs operating in this temperature range are usually based on chromium-containing alloys (stainless steels), [4][5][6] the stability of these cathodes vs. Cr-poisoning is a key issue. [7][8][9][10][11][12][13][14][15][16][17][18][19] Especially the long-term decrease in the initial high performance of the cathode due to the gas-phase transport of volatile Crspecies and their reaction with the cathode is currently one of the main obstacles for the increase in life-time and reliability of SOFCs. 9,12,14,15 Nevertheless, long-term in-situ studies on the kinetic parameters for oxygen exchange vs. chromium poisoning under defined conditions are scarce.…”
mentioning
confidence: 99%
“…Aside from the aforementioned driving forces, other macroscopic factors like cathode polarization also tend to influence Cr-vapor deposition sites. One research group 98 deliberating flowed Cr-vapors of 10 −3 P under cathodic polarization of −100 mV and −200 mV with air for 75 h. As we influence deposition sites, higher polarization results in diverse range of product distribution in the bulk and surface of the porous LSCF electrode. The group showed that under higher polarization of cathode, formation of Sr and Cr secondary phase is promoted on the surface while Co–Fe spinel forms as the result of phase separation.…”
Section: Degradation Of Sofc Cobalt-based Perovskite Cathode Materialsmentioning
confidence: 99%
“…Since the quantitative understanding is important in the relation between the accumulated amount of Cr and potential lowering, further experiments are under way to distinguish between Cr poisoning and the loss due to the change in microstructure (5). Furthermore, AIST makes attempts for the accelerating method (6). In this effort, they clarified that Cr poisoning appears only in the electrode resistivity not in the IR loss.…”
Section: Cr Poisoningmentioning
confidence: 99%
“…Chemical reactions of SSC cathode in the disk-type planar and the Cr poisoning in LSM cathode in the segment-in-series cells were adopted to apply the accelerated method by AIST (6).…”
Section: Cathodesmentioning
confidence: 99%